Automating model construction and visualization of results of numerical simulation of deformation of nanostructures - Babichev, Alexey Vladimirovich (Computational Continuum Mechanics, 2008)
The models and results of visualization of mathematical modeling of quasi-static/dynamic deformation of a nanotube subject to twisting are presented. Automating the model construction and visualization of numerical simulation have been carried out using the software packages MSC Patran 2007 and VMD, and the programming languages PCL and TCL. The advantages and deficiencies of both software packages are illustrated by visualizing the quasi-static/dynamic deformation of the nanotube. Computations have been made using the package PIONER.